Utilization of Agricultural Waste as a Total Mixed Ratio Pellet Material for Rex Rabbit Feed - Syaefullah, Bangkit Lutfiaji; Widayati, Okti; Purwanta, Purwanta; Abdillah, Labib (Jurnal Agripet, 2024)
This study aimed to evaluate the quality of Total Mixed Ration (TMR) pellets derived from agricultural waste and assess their potential as feed for Rex rabbits. The research employed an experimental approach, utilizing agricultural and plantation waste to produce TMR pellets. The study was conducted in two stages: pellet production and rabbit feeding trials. Three formulations of TMR pellets were developed with varying concentrations of oil palm empty fruit bunches (EFB): P1 (5% EFB), P2 (10% EFB), and P3 (15% EFB). The optimal formulation was subsequently used for the feeding trials. Rabbit feed treatments included T0 (60% commercial pellet + 40% forage), T1 (40% commercial pellet + 20% TMR pellet + 40% forage), T2 (30% commercial pellet + 30% TMR pellet + 40% forage), and T3 (60% TMR pellet + 40% forage). Results from the pellet analysis indicated no significant differences in organoleptic properties among the formulations. The durability test yielded the highest value of 98.77%, while the proximate analysis of the P1 formulation showed a dry matter content of 85.67%, ash content of 10.35%, organic matter of 89.65%, crude protein of 18.65%, crude fat of 18.72%, and crude fiber of 19.18%. In the rabbit feeding trials, there were no significant differences in rabbit performance when compared to those fed with commercial pellets. Based on these findings, it can be concluded that agricultural waste can be effectively utilized as a raw material for rabbit feed pellets, offering comparable quality to commercial alternatives. This research highlights the potential of agricultural waste in reducing environmental pollution while providing an economically viable alternative for animal feed.